Open Government Data: The Key to Promoting Public Participation, and Fighting against Corruption - สังฆจันทร์ ฐาลินี (Journal of Public Administration, Public Affairs, and Management, 2021)
Poor governance resulted from corruption is a chronic problem for the public sector. Although there is an effort to involve citizens to participate in dealing with the issue, they tend to avoid such participation since they do not have sufficient data or have to face data asymmetry that may debase their opinions or arguments. However, open government data (OGD) is now being widely implemented around the world. It is expected to produce a variety of positive impacts on society. This study aimed to investigate the effects of OGD on empowering public participation (PP) and enhancing corruption control (CC). Based on data analysis of 113 countries using Partial Least Squares-Structural Equation Modelling (PLS-SEM), this study found that OGD had a positive significant effect on PP. Besides, OGD could also significantly increase effective efforts to CC. Indeed, OGD has helped citizens to increasingly participate in CC. Given the importance of OGD, countries should be aware of the development of OGD and better capitalize on its benefits and values.